Genre and Discursive Characteristics of British Restaurant Internet Discourse - E. B. Pavlova (Научный диалог, 2017)
The article is devoted to the genre stratification of the British restaurant discourse and the analysis of genre and discursive characteristics of its virtual variants. Based on understanding of the genre as the basic unit of discourse, the author classifies the genres depending on the scope of speech that supports a particular view of the restaurant business, including restaurant Internet communication. The article highlights the speech genres of the advertising restaurant discourse; restaurant media discourse; restaurant Internet discourse; commercial restaurant discourse; restaurant discourse of the business community. The author makes a conclusion about the special place of hypergenre of catering Internet-site, as the Internet site, being one of the genres of restaurant Internet discourse, can act as a special hypertext space joining such online genres as blog, review, comment etc. The work describes the discursive features of restaurant Internet discourse, the classification of types of verbalization of the sender in a website hypertext space (personalized sender; collective personalized sender; the collective sender (team) with elements of personification; the collective sender (team) without personification). The work also identifies socio-economic, status-role, social-demographic, socio-personal discursive parameters of the addressee. The article contributes to the development of discourse studies and the theory of Internet communication.